First you want to get y by itself for each equation.
2. 2x + y = -7 -----> y = -7 - 2x
x - 2y = -4 -------> y = 2 + 1/2x
4x - y = 5 ---------> y = 4x - 5
The first two equations are perpendicular to each other because the slopes are complete opposites. (for a slope to be perpendicular to another the slope, the sign and the number have to be flipped)
For example:
the slope is -2
the perpendicular slope is 1/2 (positive one half)
the slope is 4/5
the perpendicular slope is -5/4
3. y = 3x
6x - 2y = 7 -----> y = 3x - 7/2
3y = 9x - 1 -----> y = 3x - 1/3
All of these equations are parallel to each other because all of their slopes are the SAME (same slope = parallel).